Economic Empowerment of the Ummah through Strengthening the Business Partnership of Pondok Pesantren Mambaul Khoirat Ketapang in Ketapang Regency - Abdullah AF; Muslimin H Kara; Rahman Ambo Masse; Budi Iswanto (Pascasarjana, Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This research discusses the role of the Mambaul Khoirat Islamic Boarding School in empowering the people's economy through strengthening business partnerships in Ketapang Regency. As an Islamic-based educational institution, this Islamic boarding school not only focuses on religious learning, but also plays a role in improving the economic welfare of the surrounding community. This study analyzes Islamic boarding school strategies in building partnerships with various parties, including local business actors, as well as their impact on the economic independence of students and the community. The research results show that Islamic boarding schools adopt a holistic approach through entrepreneurship training, community-based business management, and strengthening sustainable business networks. The developed business partnerships provide wider access to markets and economic resources, thereby increasing the community's competitiveness and economic independence. Thus, strengthening business partnerships at the Mambaul Khoirat Islamic Boarding School has proven to be an effective model of economic empowerment in supporting the welfare of the community based on Islamic values.